Quotient groups of locally graded groups and groups of certain Kurosh-Chernikov classes - Trebenko, D. Ya.; Chernikov, N. S. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We establish the validity of the inclusion G/N∈ X for groups G ∈ X under certain restrictions on N ⊴ G, where X is one of the following classes, the class of locally graded groups, the class of RI-groups, or the class \(PY\) for a fixed group variety \(Y A\) .